Economics of Climate-Smart Agriculture : Considerations for Economic and Financial Analyses of Climate-Smart Agriculture Projects - World Bank (World Bank, Washington, DC, 2019)
Climate change poses a major threat to food systems and livelihoods all over the world. Climate-smart agriculture (CSA) addresses these challenges. CSA stands for including climate change into the planning and implementation of sustainable agricultural strategies. More specifically, CSA has three objectives to achieve these overarching goals: (1) sustainably increasing agricultural productivity to support equitable increases in incomes and food security; (2) adapting and building resilience to climate change from the farm to national levels; and (3) developing opportunities to reduce GHG emissions from agriculture (FAO 2013). The report is structured as follows: the report starts with a brief overview of the framework for economic and financial analyses in section two; section three, provides an overview of benefit and cost categories that are relevant for CSA; section four, provides descriptions of 10 salient features of CSA as may be relevant for EFAs; section five, presents findings of the review of 10 EFAs of agriculture lending projects; section six, provides a brief overview of techniques or tools that could support the presentation of CSA in EFAs; and section seven concludes.